Research on the Pathway for Constructing Doctor-Patient Interpersonal Trust - Chenyi XU; Xiaoshan HUANG; Yanyan JIN (Yixue yu zhexue, 2025)
Situation is the foundation for the trust-building among doctors and patients. In Dewey's situational philosophy theory, doctor-patient trust construction can be divided into individual, interactive and social aspects from the horizontal practical dimension, and into difficult, problematical and coordinating situation from the vertical theoretical dimension. Through in-depth interactions with medical social workers and medical staff at S Hospital, it can be concluded that the negative personal experience acquired by doctors and patients in difficult situations hinders the accumulation of interactive experience in problematical situations. Therefore, it can be said that medical social workers play an important role in promoting the generation of coordinating situations. With the aid of the mode of "observation + action", which helps to promote the accumulation of doctor-patient trust experience, medical social workers would make great effects in creating humanistic medical situations, sharing empathetic knowledge, as well as transmitting the concept of mutual respect and love.